Effects of Micro-credit, Micro-savings and Training on the Growth of Small and Medium Enterprises in Machakos County in Kenya - Kisaka, Sifujo E.; Mwewa, Naomi M. (Research Gate, 2014)
The objective of every micro-entrepreneur is to grow their businesses into large enterprises. To achieve this, most of the micro-entrepreneurs make use of microfinance services and training to improve their productivity and profitability. Many studies have been done in Kenya on SMEs and how they are influenced by microfinance services but none had focused on the effects of microfinance services on the growth of the SMEs. The purpose of this study was to find out the effects of micro-credit, micro-savings and training on the growth of SMEs in Machakos County. A survey research design was applied to study 8 types of business categories in Machakos County. Structured questionnaire was used to collect data from 100 businesses. Multiple regression analysis was used to determine the relationships between micro-credit, micro-savings, training and growth of SMEs. The results show that micro-credit, micro-savings and training jointly contribute positively to SMEs growth. However, the effect of training is not statistically significant. This could be attributed to training that is not based on the real needs of SMEs.
Keywords: Small and medium enterprises (SMEs)